Dinuclear zinc catalysts with unprecedented activities for the copolymerization of cyclohexene oxide and CO21. Issue 22 (18th March 2015) - Kissling, S.; Lehenmeier, M. W.; Altenbuchner, P. T.; Kronast, A.; Reiter, M.; Deglmann, P.; Seemann, U. B.; Rieger, B.
<x xml:space="preserve">Abstract</x> New dinuclear zinc catalysts reveal by far the highest polymerization rates for the copolymerization of cyclohexene oxide and CO2.